Subsurface Fault Geometry Model Based on Type Resistance Data (Laboratory Scale Review) - Yanto, M.F.W; Muin , M. R.; Th. Musa , Moh. Dahlan; Rusydi. H , M.; Sandra; Badaruddin (LPPM Universitas Tadulako, 2021)
Introduction: Research has been carried out with the title